IMPLEMENTASI TEORI BELAJAR DALAM PENDIDIKAN MATEMATIKA SEKOLAH DASAR - Sarjiman, P (Dinamika Pendidikan, 2015)
The development of the country depends on the human resource qualification. Indonesia is one of the developing countries which is in the proecess of its human resource development. The goverment had decided to allocate 20% of the national budget in the National Education Department. The elementary school teachers should be bachelor degree (S-1), and the sertication program is carried out. Mathematical Eduction in Elementary Schools faced many obstacels, among them are the mastery weaknesses of the elementary school teachers about mathematics related to the mathematics taught in the elementary schools and the methods as well as strategies implemented in the elementary schools. Relating to the last weakness is that the poor of implementing learning teories in teaching mathematics. In ths paper, there will be only the learning theories considered to be suitable for the teaching/learning mathematics: those are constructivism, Bruner 'theory, and VanHiele's theory. Elementary students should be active in constructing the mathematical concept (constructivism), Buner's theory is we/known about the term oj inactive, iconic and symbolic. Blsides, Bruner also performed the constructivism, contrast and variation theorem, notation, and connectivity theorem. Where as Van Hiele theory stated that there are 5 grades in the development of learning geometry, namely visualization, analuis, informal deduction, deduction and rigor. The elementary school teachers should master the theories oj learning as many as possible in order to be able to teach well. One theory is suitable for a certain mathematics material but not always suitablefor other materials. Key words: Educational Quality, Learning Theories, Mathematical Eduacation